Healthy Lifestyles of University Students in China and Influential Factors - Dong Wang; Xiao-Hui Xing; Xian-Bo Wu (The Scientific World Journal)
This study was conducted to analyze to what extent university students exhibit healthy lifestyles and which sociodemographic variables influence healthy lifestyles. 4809 university students randomly selected were measured by use of the Healthy Lifestyle Scale for University Students questionnaire. When controlling for the other variables, the total healthy lifestyles score was predicted by gender, grade, father’s level of education, and type of institution; exercise behaviour was partially predicted by gender, grade, type of institution, and family monthly income; regular behaviour was modulated by gender, grade, type of institution, family monthly income, and father’s educational level; nutrition behaviour was partially affected by type of institution, family monthly income, and father’s educational level; health risk behaviour was modulated by gender, mother’s level of education, and family monthly income; health responsibility was modulated by gender, grade, type of institution, and father’s educational level; social support was modulated by gender, grade, and father’s educational level; stress management was modulated by gender, grade, type of institution, and mother’s education level; life appreciation was modulated by grade, type of institution, and mother’s educational level. These influences should be taken into account in designing interventions for specific socio-demographic profiles that might be at higher risk for certain behaviours.